2014
DOI: 10.1128/mbio.01978-14
|View full text |Cite
|
Sign up to set email alerts
|

CD8 T Cells in Innate Immune Responses: Using STAT4-Dependent but Antigen-Independent Pathways to Gamma Interferon during Viral Infection

Abstract: The cytokine gamma interferon (IFN-γ), with antimicrobial and immunoregulatory functions, can be produced by T cells following stimulation through their T cell receptors (TCRs) for antigen. The innate cytokines type 1 IFNs and interleukin-12 (IL-12) can also stimulate IFN-γ production by natural killer (NK) but not naive T cells. High basal expression of signal transducer and activator of transcription 4 (STAT4), used by type 1 IFN and IL-12 to induce IFN-γ as well as CD25, contributes to the NK cell responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
23
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 50 publications
4
23
0
2
Order By: Relevance
“…Eight days after LCMV infection, NK cell-mediated IFN-␥ responses to inflammatory cytokines were reduced, and this is in contrast to LCMV-specific CD8 ϩ T cells that were highly responsive to cytokine stimulation at this time point (30). Similar to observations of virus-specific CD8 ϩ T cells (30,46,47), several cytokine combinations induced CD69 and/or CD25 upregulation in a majority of NK cells (e.g., IL-18 plus IFN-␤) but only triggered IFN-␥ production in a more limited subset of the NK cells. These differences were more pronounced in NK cells from BALB/c mice ( Fig.…”
Section: Discussionsupporting
confidence: 57%
“…Eight days after LCMV infection, NK cell-mediated IFN-␥ responses to inflammatory cytokines were reduced, and this is in contrast to LCMV-specific CD8 ϩ T cells that were highly responsive to cytokine stimulation at this time point (30). Similar to observations of virus-specific CD8 ϩ T cells (30,46,47), several cytokine combinations induced CD69 and/or CD25 upregulation in a majority of NK cells (e.g., IL-18 plus IFN-␤) but only triggered IFN-␥ production in a more limited subset of the NK cells. These differences were more pronounced in NK cells from BALB/c mice ( Fig.…”
Section: Discussionsupporting
confidence: 57%
“…The notion that T cells can perform as innate cells has been previously proposed and debated in a number of reports (6, 7, 14, 15, 37–39). While the role of NK cells producing IFNγ during the early phase of Listeria infection is indisputable, Anderson et al showed evidence of early IFNγ production in the absence of NK cells (37).…”
Section: Discussionmentioning
confidence: 99%
“…Ruiz et al identified this population of memory CD8 + T cells as NK1.1 + CD8 + T cells (13). Similarly lymphocytic choriomeningitis virus (LCMV)-primed memory CD8 + T cells were able to rapidly produce innate IFNγ upon infection with murine cytomegalovirus (MCMV) infection in an antigen-independent manner (15). However, these innate capabilities were identified in the context of prior pathogen exposure.…”
Section: Introductionmentioning
confidence: 99%
“…STAT6 has also been proved to promote the antiviral response of innate cells by inducing specific target genes responsible for immune cell homing (21). STAT4, which mediates IL-12-induced signaling pathway, has been reported to limit kinds of viral infection in host, such as lymphocytic choriomeningitis virus (22,23), murine CMV virus (24), and HSV-2 (25). Moreover STAT4-dependent IFN-g production is protective for host during virus infection (22)(23)(24)(25).…”
mentioning
confidence: 99%
“…STAT4, which mediates IL-12-induced signaling pathway, has been reported to limit kinds of viral infection in host, such as lymphocytic choriomeningitis virus (22,23), murine CMV virus (24), and HSV-2 (25). Moreover STAT4-dependent IFN-g production is protective for host during virus infection (22)(23)(24)(25). However, the role of STAT4 in regulating the innate sensing of invading pathogens and subsequent activation of innate signaling for initiating antiviral innate immune response remains unclear.…”
mentioning
confidence: 99%